Elaboração de marcadores pedagógicos como subsídio para construção de projeto político pedagógico para o ensino superior em enfermagem - Mix, Paulo Roberto (Universidade do Vale do Rio dos Sinos, 2016)
The objective of this qualitative study is to propose pedagogical markers that support the development of a pedagogical political project (PPP) for a degree course in nursing in the municipality of Santa Rosa. The data were collected using the focus group technique, which in turn utilized the square formation device for health, including participants from the areas of education, management, and social control; a total of eight participants represented the four sides of the square. Three sessions were held, the audio was recorded and subsequently transcribed, and the content analysis technique was used to analyze the data. Four pedagogical markers that affect the training of nurses emerged: Commitment to the SUS [Brazilian Unified Health Care System], Completeness of attention to health, Accountability in health care processes, and Management and leadership. Here we present a proposal for a base curriculum that will serve as a suggestion for implementing a nursing course from the perspective of reinforcing political and social commitment and meeting the requirements of new training models for higher education. In order for the proposed base curriculum to allow a new training mode for nurses, it is fundamental that this training process be guided by the health needs of the population, be integrated into the training with effective and two-way service, constructing a solid foundation to transform care practices and the work process, while understanding that complete care will truly be a reality once we understand the users and their problems as the center of health care.
Keywords: Educação; Formação em enfermagem; Integralidade da atenção; Currículo; Education; Training in nursing; Complete care; ACCNPQ::Ciências da Saúde::Enfermagem